Joint patch clustering-based adaptive dictionary and sparse representation for multi-modality image fusion - Wang, Chang; Wu, Yang; Yu, Yi; Zhao, Jun Qiang (Machine vision and applications, 2022)
For the image fusion method using sparse representation, the adaptive dictionary and fusion rule have a great influence on the multi-modality image fusion, and the maximum L 1 norm fusion rule may cause gray inconsistency in the fusion result. In order to solve this problem, we proposed an improved multi-modality image fusion method by combining the joint patch clustering-based adaptive dictionary and sparse representation in this study. First, we used a Gaussian filter to separate the high- and low-frequency information. Second, we adopted the local energy-weighted strategy to complete the low-frequency fusion. Third, we used the joint patch clustering algorithm to reconstruct an over-complete adaptive learning dictionary, designed a hybrid fusion rule depending on the similarity of multi-norm of sparse representation coefficients, and completed the high-frequency fusion. Last, we obtained the fusion result by transforming the frequency domain into the spatial domain. We adopted the fusion metrics to evaluate the fusion results quantitatively and proved the superiority of the proposed method by comparing the state-of-the-art image fusion methods. The results showed that this method has the highest fusion metrics in average gradient, general image quality, and edge preservation. The results also showed that this method has the best performance in subjective vision. We demonstrated that this method has strong robustness by analyzing the parameter’s influence on the fusion result and consuming time. We extended this method to the infrared and visible image fusion and multi-focus image fusion perfectly. In summary, this method has the advantages of good robustness and wide application.